Optical film coating liquid and optical film
By using an optical film coating solution of aqueous polyester resin and nano-grade zirconia on optical polyester films, the balance problem between high refractive index and adhesion is solved, and the efficient ITO decompression effect is achieved, and the overall performance of the optical film is improved.
Patent Information
- Application Number
- CN202411634006.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-04-04
AI Technical Summary
While improving surface properties, it is difficult to achieve a balance between high refractive index and adhesion. Especially in ITO applications, the refractive index of existing chemical coatings is not sufficient to achieve a desalination effect.
An optical film coating solution using aqueous polyester resin and nano-grade zirconia (zirconium sol) as the main components is used to optimize the component ratio of the resin and nano-grade filled particles to achieve high refractive index and good adhesion of the coating.
It realizes the high refractive index, good adhesion and high light transmittance of the optical film, and is especially suitable for ITO detonation film, reducing the reflection loss of light on the interface and improving image quality.
Smart Images

Figure CN119752290A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of optical films, and in particular to an optical film coating liquid and an optical film. Background Art
[0002] Biaxially oriented polyester film (BOPET) has shown wide application potential in many fields due to its high strength, good rigidity, high transparency and glossiness, as well as its odorless, tasteless, colorless, non-toxic and outstanding toughness. From traditional packaging, printing, window film, solar backplane, to high-end optical films such as anti-reflection film, prism film, diffusion film and hardened film, BOPET film has become an indispensable material. Although the surface properties of ordinary BOPET film such as printing, lamination and vacuum aluminum plating can meet general process requirements, for optical polyester films with higher requirements on surface properties, additional chemical treatment is still required to enhance the adhesion between the film and the glue.
[0003] As an effective method to improve the surface properties of BOPET film, coating can significantly improve its surface properties by coating a layer of polymer solution on the surface of the film. This process is usually carried out between the longitudinal drawing machine (MDO) and the transverse drawing machine (TDO) through an online coater. The longitudinally stretched PET film immediately enters the online coater for coating with a polymer solution, and then enters the TDO for transverse stretching. During the stretching process, the solvent evaporates, leaving a layer of polymer on the surface of the film, thereby achieving the purpose of improving the surface properties.
[0004] However, although the coating method has achieved results in improving the surface properties of BOPET film, it still faces many challenges in the specific application of optical polyester film. For example, in addition to the performance of general polyester film, optical polyester film also needs to be coated with a primer layer to achieve high transmittance, low haze, good adhesion, scratch resistance and anti-glare properties. However, the refractive index of ordinary chemical coatings is often lower than 1.60, which cannot achieve the shadow elimination effect in ITO (indium tin oxide) applications. At the same time, as the refractive index increases, the adhesion between the Primer layer and the UV light-curing glue will also be affected. Therefore, choosing the right resin and cross-linking agent and adjusting the formula to balance the refractive index and adhesion have become urgent problems to be solved. Summary of the invention
[0005] The purpose of the present application is to provide an optical thin film coating liquid, which can be coated on the surface of an optical polyester film through an online coating technology, not only making the polyester film have excellent optical properties (such as high refractive index), smoothness and adhesion, but also being particularly suitable for ITO anti-shadow film, achieving a dual improvement in refractive index and adhesion. The purpose of the present application is achieved through the following technical solution, the optical thin film coating liquid includes a resin and nano-scale filling particles, the resin and the nano-scale filling particles are used as the main components; The resin includes water-based polyester resin and amino resin; The nano-scale filling particles include zirconium oxide, and the zirconium oxide is in the form of zirconium sol; Among them, the component ratios within the main component are as follows: a) 20-90wt% water-based polyester resin; b) 5-50 wt% zirconium sol; c) 5-30wt% amino resin.
[0006] In one embodiment, it also includes a wetting agent, a pH adjuster, and deionized water.
[0007] In one embodiment, the total amount of the resin is 2-15wt%, the weight percentage of the nano-scale filler particles is 0.01-5wt%, and the weight percentage of the wetting agent and pH adjuster is 0.0005-0.005wt%.
[0008] In one embodiment, the resin includes one or more structures of fluorene ring, naphthalene ring and benzene ring.
[0009] In one embodiment, the resin also includes a water-soluble group.
[0010] In one embodiment, the polyester resin material includes one or more of succinic acid, cyclic ester dicarboxylic acid, terephthalic acid, naphthalene dicarboxylic acid, 9,9-bis[4-(2-acryloyloxyethoxy)phenyl]fluorene, sulfonic acid isophthalic acid, and one or more of ethylene glycol, propylene glycol, 1,6-hexanediol, propylene glycol, 1,4-cyclohexanedimethanol, 1,2-butanediol, and the polyester resin is formed by esterification reaction and then polycondensation.
[0011] In one embodiment, the particle size distribution of the nano-scale filling particles is 10-100 nm.
[0012] In addition, the present application also provides an optical film, including a substrate layer and a primer layer formed on the substrate layer, wherein the primer layer is formed by coating the aforementioned optical film coating liquid.
[0013] In one embodiment, the refractive index of the primer layer and the substrate layer is the same.
[0014] In one of the embodiments, a transparent conductive layer is also included.
[0015] Compared with the prior art, this application has the following beneficial effects: The optical film coating liquid of the present application uses water-based polyester resin and nano-scale zirconium oxide (zirconium sol) as main components to achieve precise matching of the coating refractive index with the PET base film refractive index, both reaching about 1.67, which not only optimizes the optical properties, such as high refractive index, but also avoids the reflection loss of light on the film interface, thereby improving the light transmittance and clarity of the optical film. At the same time, the introduction of nano-zirconium oxide also enhances the wear resistance and hardness of the film, extending its service life.
[0016] The combination of water-based polyester resin with excellent water dispersibility and nano-scale filler particles, and the addition of amino resin, effectively enhances the adhesion between the coating and the PET base film, as well as the resistance to UV oxidation, so that the coating can still maintain a good adhesion state when subjected to environmental changes or external forces, and is not easy to fall off or crack. In addition, by optimizing the ratio of resin to nanoparticles, the coating liquid shows excellent online coating stability, ensuring the uniformity and consistency of the coating thickness, and further improving the overall quality of the product.
[0017] Adding an appropriate amount of wetting agent and pH regulator to the coating liquid can not only improve the fluidity of the coating liquid, making it easier to form a uniform and dense coating on the PET base film, but also improve the operability of the coating process and reduce production costs. At the same time, the addition of these additives does not have a negative impact on the optical properties and adhesion of the coating, ensuring the comprehensive performance of the final product.
[0018] The optical thin film coating liquid of the present application is particularly suitable for preparing ITO shadow-eliminating film. Due to the excellent adhesion and refractive index matching between the coating and the PET base film, as well as the high light transmittance and stability of the coating itself, ITO can form a uniform conductive layer after sputtering, effectively eliminating moiré fringes and improving the image quality of the display. This feature makes the optical film of the present application have a wide range of application prospects in the fields of high-end electronic products such as touch screens and liquid crystal displays. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 It is a schematic diagram of the structure of the optical film in the embodiment of the present application.
[0020] Explanation of reference numerals: 100, substrate layer; 200, primer layer; 300, transparent conductive layer. DETAILED DESCRIPTION
[0021] In order to make the above-mentioned purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are described in detail below in conjunction with the accompanying drawings. It is to be understood that the specific embodiments described herein are only used to explain the present application, rather than to limit the present application. It should also be noted that, for ease of description, only some structures related to the present application are shown in the accompanying drawings, rather than all structures. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0022] The terms "including" and "having" and any variations thereof in this application are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device comprising a series of steps or units is not limited to the listed steps or units, but may optionally include steps or units not listed, or may optionally include other steps or units inherent to these processes, methods, products or devices.
[0023] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0024] With the advancement of science and technology and the expansion of applications, the performance requirements for optical films are becoming increasingly higher, especially in terms of high refractive index, high adhesion, high light transmittance and environmental protection. More stringent standards have been proposed. In order to meet these requirements, the optical film coating liquid is a key material for the preparation of high-performance optical films, and the optimization of its formulation and preparation process has become a hot topic of research. The optical film coating liquid is usually composed of multiple components such as resin, nano-scale filler particles, additives, etc. Through a specific ratio and preparation process, a coating with excellent optical properties and adhesion can be formed on the surface of the optical film. This coating can not only improve the overall performance of the optical film, but also give it specific functions, such as anti-reflection, anti-reflection, and shadow elimination. This application will discuss in detail the optical film coating liquid and the optical film made thereof. The optical film coating liquid of this application includes resin and nano-scale filler particles. The resin and the nano-scale filler particles are the main components. The resin includes water-based polyester resin and amino resin. The nano-scale filler particles include zirconium oxide, and the zirconium oxide exists in the form of zirconium sol. The component ratios within the main component are as follows: a) 20-9wt% water-based polyester resin; b) 5-50 wt% zirconium sol; c) 5-30wt% amino resin.
[0025] The optical thin film coating liquid of the present application uses water-based polyester resin and amino resin as the main components of the resin. Water-based polyester resin is known for its good water dispersibility, film-forming property and optical properties. Amino resin can be used as a cross-linking agent to chemically react with water-based polyester resin through its active functional groups to form a stable cross-linked network structure, thereby improving the adhesion and weather resistance of the coating. In terms of nano-scale filling particles, the present application uses zirconium oxide as a filling material and prepares it in the form of zirconium sol. Zirconium sol has the advantages of small particle size, uniform distribution, and good dispersibility, which improves the density and hardness of the coating. At the same time, the high refractive index characteristics of zirconium oxide can also significantly improve the refractive index of the coating, so that it can achieve better refractive index matching with optical materials such as PET base film, reduce the reflection loss of light at the interface, and improve the light transmittance and clarity of the optical film.
[0026] The present application has made optimizations in the proportion of components within the main component. Specifically, the content of the water-based polyester resin is controlled between 20 and 90 wt%. This proportion range not only ensures the film-forming property and optical properties of the resin matrix, but also provides sufficient space for the addition of other components. The content of zirconium sol is controlled between 5 and 50 wt%. Zirconium sol is a uniform solution formed by dispersing zirconium oxide in a solvent. The specific solvent is not limited, as long as the nano zirconium oxide can be fully dispersed. The ratio range of zirconium oxide and solvent that can form zirconium sol can be used as the zirconium sol in this main component. By adding zirconium sol to ensure a high refractive index, the negative impact of excessive filling particles on the optical properties of the coating can be avoided. The content of amino resin is controlled between 5 and 30 wt% to provide sufficient cross-linking points and adhesion while maintaining the flexibility and processing performance of the coating.
[0027] Through the optimization of the combination of resin and nano-scale filling particles, as well as a reasonable component ratio, the coating liquid of the present application can prepare an optical film with high refractive index, high light transmittance and low reflection loss, meeting the high requirements of high-end optical devices for optical performance. The cross-linking effect of the amino resin and the filling effect of the zirconium sol jointly improve the adhesion and weather resistance of the coating, so that the optical film can maintain good performance stability during long-term use. The optical film coating liquid of the present application achieves a comprehensive improvement in optical performance, adhesion and weather resistance through a carefully designed combination system of resin and nano-scale filling particles, as well as a reasonable component ratio.
[0028] Specifically, it also includes a wetting agent, a pH regulator, and deionized water. On the basis of the main components composed of resin and nanometer-scale filler particles, a wetting agent, a pH regulator, and deionized water are added. The addition of these components can not only further optimize the performance of the coating liquid, but also improve the overall quality of the coating. The wetting agent, as a surfactant, can significantly reduce the surface tension between the coating liquid and the substrate, making it easier for the coating liquid to spread on the surface of the substrate to form a uniform and dense coating, which not only improves the uniformity and coverage of the coating, but also reduces defects such as bubbles and pinholes during the coating process, thereby improving the optical properties and appearance quality of the optical film. The pH regulator is used to adjust the pH of the coating liquid to ensure that it is within an appropriate range. The appropriate pH value can not only maintain the stability of the coating liquid, prevent adverse reactions and precipitation between components, but also optimize the cross-linking reaction of the coating, and improve the adhesion and weather resistance of the coating. Deionized water is the main solvent of the coating liquid. In addition to the above materials, the balance is deionized water.
[0029] Specifically, the total amount of the resin is 2-15wt%, the weight percentage of the nano-scale filling particles is 0.01-5wt%, and the weight percentage of the wetting agent and pH adjuster is 0.0005-0.005wt%. When preparing the optical film coating liquid of the present application, the weight percentage of each component is precisely controlled to ensure the performance of the coating liquid and the quality of the final coating, wherein the total amount of the resin is limited to the range of 2-15wt%, the weight percentage of the nano-scale filling particles is controlled between 0.01-5wt%, and the weight percentage of the wetting agent and pH adjuster is finely adjusted within the range of 0.0005-0.005wt%. As the main film-forming substance of the coating liquid, the content of resin directly affects the thickness, hardness and optical properties of the coating. In the present application, the total percentage of resin is controlled within the range of 2~15wt%. This ratio not only ensures that the resin can fully form a film to form a coating with a certain strength and hardness, but also avoids the problems of excessively thick coating and decreased light transmittance caused by excessive resin content. As an important modifier in the coating liquid, the content of nano-scale filling particles has a significant effect on the refractive index, wear resistance and scratch resistance of the coating. In the present application, the weight percentage of nano-scale filling particles is controlled between 0.01~5wt%. This ratio not only ensures that the filling particles can be effectively dispersed in the resin matrix and improve the refractive index of the coating, but also avoids the problems of uneven coating and easy cracking caused by excessive filling particle content.
[0030] As auxiliary additives in the coating liquid, the content of wetting agent and pH regulator plays an important role in the stability of the coating liquid and the adhesion and weather resistance of the coating. In the present application, the weight percentage of wetting agent and pH regulator is adjusted within the range of 0.0005~0.005wt%. This ratio not only ensures that the coating liquid has good fluidity and wettability, so that the coating can be evenly covered on the surface of the substrate, but also avoids the problems of reduced coating performance and increased cost caused by excessive additive content. By accurately controlling the weight percentage of resin, nanometer-scale filler particles, wetting agent and pH regulator, the coating liquid of the present application can prepare a coating with excellent optical properties, good adhesion and weather resistance, meet the high requirements of high-end optical films for coating performance, and maximize cost-effectiveness by reasonably adjusting the content of each component while ensuring the coating performance.
[0031] The amino resin includes urea-formaldehyde resin, melamine formaldehyde resin and aniline formaldehyde resin. The wetting agent may include one or more of TEGO® Wet505 (Di Gao), AEROSOL® OT-75 (Cytec), Surfynol® 104BC (AIR PRDOUCTS), Surfynol® 504 (AIR PRDOUCTS), DOWFA optical film coating liquid TM 2A1 (Dow Chemical Company). The pH regulator is an amine compound, such as at least one of 2-amino-2-methyl-1-propanol, ammonia, diethanolamine and triethanolamine. The aqueous coating liquid can be coated on the polyester film by in-line coating (ILC). After coating, the polyester film has excellent optical properties (high refractive index), smoothness and adhesion, and is suitable for application in optical polyester films such as ITO films.
[0032] Specifically, the resin includes one or more structures containing fluorene ring, naphthalene ring and benzene ring. The resin containing fluorene ring, naphthalene ring and benzene ring structure is selected as the main film-forming material. The introduction of these structures can not only improve the thermal stability and chemical stability of the resin, but also give the coating excellent optical properties and mechanical properties. Fluorene ring, naphthalene ring and benzene ring are typical structures in aromatic compounds, with high conjugated energy levels and stable chemical properties. The presence of these structures in the resin enhances the interaction between the resin molecular chains, thereby improving the thermal stability and chemical stability of the resin, which means that the coating liquid can better maintain its stable performance during preparation and storage. In addition, the introduction of these special structures also significantly improves the optical properties of the coating. The conjugated structures of fluorene ring, naphthalene ring and benzene ring make the resin molecules show a higher refractive index when absorbing light energy, thereby improving the refractive index of the coating. At the same time, these structures also make the resin molecules less prone to photodegradation when exposed to light, maintaining the good light transmittance and light resistance of the coating.
[0033] Specifically, the resin also includes water-soluble groups, such as -COOH, -SO3Na, etc. These water-soluble groups not only give the resin good water solubility and dispersibility, but also improve the processing performance of the coating liquid and the optical properties and adhesion of the final coating. The introduction of water-soluble groups enables the resin to form a stable dispersion system in water, avoiding the agglomeration and precipitation of resin particles, thereby ensuring the uniformity and stability of the coating liquid, ensuring uniform coverage and good adhesion of the coating on the substrate. In addition, the water-soluble groups also enhance the interaction between the resin and the substrate, and improve the adhesion of the coating.
[0034] Specifically, the polyester resin material includes one or more of succinic acid, cyclic ester dicarboxylic acid, terephthalic acid, naphthalene dicarboxylic acid, 9,9-bis[4-(2-acryloyloxyethoxy)phenyl]fluorene, sulfonic acid isophthalic acid, and one or more of ethylene glycol, propylene glycol, 1,6-hexanediol, propylene glycol, 1,4-cyclohexanedimethanol, 1,2-butanediol, and then undergoes esterification reaction and polycondensation to form a polyester resin. That is, a small molecule with a carboxylic acid group and a polyol are selected for esterification reaction. In the esterification reaction stage, the carboxylic acid and the polyol are heated in the presence of a catalyst to form an ester bond (-COO-), connecting the acid molecule with the alcohol molecule. Subsequently, through the polycondensation reaction, that is, the process of removing small molecule water or alcohol, the polymer chain length is further increased to form a high molecular weight polyester resin. By selecting different types of carboxylic acids and polyols, the properties of the polyester resin, such as hardness, toughness, heat resistance and solvent resistance, can be customized to meet the specific needs of different application fields.
[0035] Specifically, the particle size distribution of the nano-scale filler particles is 10-100nm, preferably 10-20nm, 80-100nm, that is, it contains particles with two particle size ranges of 10-20nm and 80-100nm at the same time. The nano-scale filler particles can also include nanoparticles formed by silicon dioxide. In a preferred technical solution, the amount of the nano-scale fine particles added is preferably 10-50wt%, and more preferably 20-40wt%. The nano-scale filler particles are not limited to a specific type, but can also include nanoparticles formed by silicon dioxide (SiO2). Silica nanoparticles are ideal for improving the wear resistance, heat resistance and optical transparency of materials due to their high hardness, high chemical stability, good dispersibility and adjustable surface properties. In addition, SiO2 nanoparticles can also form chemical bonds with other material components through the hydroxyl (-OH) functional groups on their surface, further enhancing the overall performance of the material. In order to maximize the reinforcing effect of nanoparticles and avoid processing difficulties or performance degradation that may be caused by excessive addition, the recommended addition amount is further preferably 20~40wt%. Within this addition amount range, the nanoparticles can be effectively dispersed in the matrix material to form a uniform network structure, thereby significantly improving the mechanical strength, hardness, heat resistance and wear resistance of the material, while maintaining good processing performance and cost-effectiveness. By precisely controlling the particle size distribution and addition amount of nanoparticles, fine regulation of material properties can be achieved, such as enhancing mechanical strength, improving heat resistance and wear resistance, while maintaining good processing performance.
[0036] In addition, the present application also provides an optical film, including a substrate layer 100 and a primer layer 200 formed on the substrate layer 100, wherein the primer layer 200 is formed by coating the aforementioned optical film coating liquid. The film is composed of a substrate layer 100 and a primer layer 200 coated on the substrate layer 100, and the primer layer 200 is formed by curing the aforementioned optical film coating liquid through a specific process, making full use of the advantages of the coating liquid in the formulation, such as the precise particle size distribution and preferred addition ratio of the nano-scale filler particles, and also through the coating structure design, achieving significant improvement and multifunctionality in the performance of the optical film. The substrate layer 100 serves as the supporting structure of the optical film, and the primer layer 200 is attached to the surface of the substrate layer 100 through a fine coating process. The nano-scale filler particles in the primer layer 200 and their optimized distribution and addition amount can improve the surface hardness, wear resistance, and scratch resistance of the film, while maintaining excellent light transmittance and optical uniformity, which is crucial to improving the durability and extending the service life of the optical film.
[0037] Specifically, the refractive index of the primer layer 200 and the substrate layer 100 is similar, preferably, the refractive index of the primer layer 200 and the substrate layer 100 is the same. This design solves the problem that the refractive index of the primer layer 200 in the traditional optical film is low and it is difficult to be effectively applied to optical elements with high refractive index requirements, such as ITO (indium tin oxide) shadow-eliminating film. ITO shadow-eliminating film is widely used in the fields of display, touch screen and solar cell, and requires the optical film layer in contact with it to have a refractive index matching it to avoid significant reflection or scattering of light at the interface, thereby ensuring efficient transmission of light and clear display of images. In the traditional design, the refractive index of the primer layer 200 is lower than that of the substrate layer 100 or the ITO shadow-eliminating film, which often causes unnecessary reflection of light at the interface between the coating and the substrate or the ITO layer, which not only reduces the light transmittance of the optical device, but also may cause visual interference, such as "ghosting" or "glare", which seriously affects the performance and application effect of the optical film. The optical thin film coating liquid of the present application can be designed to have the same refractive index as the base layer 200 and the substrate layer 100, thereby effectively reducing the reflection of light at the interface between the two, reducing light loss, improving the light transmittance of the optical film, and ensuring the performance of optical elements such as ITO anti-shadow film.
[0038] Specifically, it also includes a transparent conductive layer 300, which is formed on a side of the primer layer 200 opposite to the substrate layer 100, and can be specifically applied as an ITO image eliminating film.
Claims
1. An optical thin film coating liquid, characterized in that: It comprises resin and nanometer-scale filling particles, wherein the resin and the nanometer-scale filling particles are main components; The resin includes water-based polyester resin and amino resin; The nano-scale filling particles include zirconium oxide, and the zirconium oxide is in the form of zirconium sol; Among them, the component ratios within the main component are as follows: a) 20-90 wt % of a water-based polyester resin; b) 5 to 50 wt % zirconium sol; c) 5 ~ 30 wt % of amino resin.
2. The optical thin film coating liquid according to claim 1, characterized in that: It also includes a wetting agent, a pH adjuster, and deionized water.
3. The optical thin film coating liquid according to claim 2, characterized in that: The total amount of the resin is 2-15wt%, the weight percentage of the nanometer-scale filling particles is 0.01-5wt%, and the weight percentage of the wetting agent and the pH adjuster is 0.0005-0.005wt%.
4. The optical thin film coating liquid according to claim 1, characterized in that: The resin includes one or more structures of fluorene ring, naphthalene ring and benzene ring.
5. The optical thin film coating liquid according to claim 4, characterized in that: The resin also includes a water-soluble group.
6. The optical thin film coating liquid according to claim 1, characterized in that: The polyester resin material includes one or more of succinic acid, cyclic ester dicarboxylic acid, terephthalic acid, naphthalene dicarboxylic acid, 9,9-bis[4-(2-acryloyloxyethoxy)phenyl]fluorene, sulfonic acid isophthalic acid, and one or more of ethylene glycol, propylene glycol, 1,6-hexanediol, propylene glycol, 1,4-cyclohexanedimethanol, 1,2-butanediol, which are subjected to esterification reaction and then polycondensed.
7. The optical thin film coating liquid according to claim 1, characterized in that: The particle size distribution of the nano-scale filling particles is 10-100 nm.
8. An optical film, characterized in that: The optical film coating comprises a substrate layer (100) and a primer layer (200) formed on the substrate layer (100), wherein the primer layer (200) is formed by coating the optical film coating liquid according to any one of claims 1 to 7.
9. The optical film according to claim 8, characterized in that: The primer layer (200) and the substrate layer (100) have the same refractive index.
10. The optical film according to claim 8, characterized in that: Also included is a transparent conductive layer (300).